Effectiveness of interpretation tool influencing the visitor outcome during visited Zoo Melaka / Louisana Balai, Vorinica Gupi Johnny and Nor Atiqah Farha Mohd Rozie - Balai, Louisana; Johnny, Vorinica Gupi; Mohd Rozie, Nor Atiqah Farha (2015)
Since the early 1990s zoos have been in a state of transformation, shifting their strategic focus from recreation and entertainment to conservation-based education in response to changing community attitudes and values. Knowledge has been viewed as an important outcome when visiting zoo. Zoo may improve their interpretation tool quality to gain visitors knowledge and outcome during visiting zoo. This shifting has been argued to elicit a crisis of identify for zoos as demand of revenue raising are at times seen to conflict with conservation initiatives. While it is not universally accepted that the foremost role of zoos as perceived by zoo management is conserved based (carr & cohen,2011), many zoos offer educational programmes designed to challenge and charge the attitudes and behaviours of visitor (smith, weiler, & ham, 2011).